Determination of TL Kinetic parameters of a phosphor - Shrivastava, Ravi; Dubey, Vikas; Saluja, Jagjeet Kaur (Recent Research in Science and Technology, 2012)
Present paper reports the methods of evaluating the kinetic parameters like trap depth, frequency factor etc. by using the Glow Curve of a phosphor. Peak shape method is found to be suitable amongst all reported methods. This method provides the nearest possible values of all studied kinetic parameters which are discussed in details. MS -Excel sheet is prepared for calculation.